A Theoretical Study of Tunable Brillouin Lasers Based on a Diamond Suspended Waveguide - Wang, Wuyue; Yu, Yu; Bai, Zhenxu; Li, Yunfei; Wang, Gong; Li, Kai; Song, Changyu; Wang, Zhiyong; Li, Sensen; Li, Yuhai; Liu, Tongyu; Yan, Xiusheng; et al. (Frontiers in Physics, 2022)
In this work we detail the design of a novel, hybrid waveguide structure which enables independent control of phonon modes and optomechanical driving forces, thereby yielding customizable Brillouin coupling over a very broad bandwidth. The Brillouin gain reaches 4400 W−1m−1, with tunable phonon frequencies from 1–95 GHz. This hybrid waveguide relies on tuning of its width and enables photon-phonon conversion based on the Brillouin nonlinear effect, and importantly, it can guide and manipulate the phonons emitted by the Brillouin effect on a chip-level device. There is hence excellent potential for this technique to be applied in microwave sources using the on-chip Brillouin photoacoustic coupling mechanism.